Biomechanics beyond the lab: Remote technology for osteoarthritis patient data—A scoping review - Hamilton, Rebecca I.; Williams, Jenny; , OATech Network+ Consortium; Holt, Cathy (Frontiers in Rehabilitation Sciences, 2022)
The objective of the project was to produce a review of available and validated technology suitable for gathering biomechanical and functional research data in patients with osteoarthritis (OA), outside of a traditional fixed laboratory setting. A scoping review was conducted using defined search terms across 3 databases (SCOPUS, OVID MEDLINE, and PEDRO) and additional sources of information from grey literature were added. One author carried out an initial title and abstract review, and 2 authors independently completed full text screenings. Out of the total 5,164 articles screened, 75 were included based on inclusion criteria covering a range of technologies in articles published from 2015. These were subsequently categorised by technology type (wearables-IMUs, wearables-other, insoles/platforms and cameras) and parameters (kinematic and spatiotemporal measures (SPTs), kinetic and SPTs, joint angles/ROM only and EMG), and as suitable for portable, part remote or fully remote use. Those technologies that are commercially available were also identified. Results concluded that from the growing number of available and emerging technologies, there is a well-established range in use. These are primarily inertial measurement units, alongside other wearables and camera-based technologies, particularly for collection of gait SPTs. Results demonstrate that biomechanical and functional remote data collection is both feasible and has growing potential for OA researchers.